Respuesta :
[tex]\begin{cases} 2x+2y=18 \\ 6x+y=39 \end{cases} \\ \\ W=\left|\begin{array}{ccc}2&2\\6&1\end{array}\right| \ W_{x}=\left|\begin{array}{ccc}18&2\\39&1\end{array}\right| \ W_{y}=\left|\begin{array}{ccc}2&18\\6&39\end{array}\right| \\ \\ W=\left|\begin{array}{ccc}2&2\\6&1\end{array}\right|=2*1-6*2=2-12=-10 \\ \\ W_{x}=\left|\begin{array}{ccc}18&2\\39&1\end{array}\right|=18*1-2*39=-60 \\ \\ W_{y}=\left|\begin{array}{ccc}2&18\\6&39\end{array}\right|=2*39-6*18=-30 [/tex]
[tex]x= \frac{W_{x}}{W} = \frac{-60}{-10}=6 \\ \\ y= \frac{W_{y}}{W} = \frac{-30}{-10}=3[/tex]
[tex]x= \frac{W_{x}}{W} = \frac{-60}{-10}=6 \\ \\ y= \frac{W_{y}}{W} = \frac{-30}{-10}=3[/tex]
6x+y=39;2x+2y=18
Solve 6x+y=39 for y:
6x+y+−6x=39+−6x(Add -6x to both sides)
y=−6x+39
Substitute (−6x+39) for y in 2x+2y=18:
2x+2y=18
2x+2(−6x+39)=18
−10x+78=18(Simplify both sides of the equation)
−10x+78+−78=18+−78(Add -78 to both sides)
−10x=−60
−10x/−10 = −60/−10(Divide both sides by -10)
x=6
Substitute (6) for x in y=−6x+39:
y=−6x+39
y=(−6)(6)+39
y=3
Answer: y = 3, x = 6
Solve 6x+y=39 for y:
6x+y+−6x=39+−6x(Add -6x to both sides)
y=−6x+39
Substitute (−6x+39) for y in 2x+2y=18:
2x+2y=18
2x+2(−6x+39)=18
−10x+78=18(Simplify both sides of the equation)
−10x+78+−78=18+−78(Add -78 to both sides)
−10x=−60
−10x/−10 = −60/−10(Divide both sides by -10)
x=6
Substitute (6) for x in y=−6x+39:
y=−6x+39
y=(−6)(6)+39
y=3
Answer: y = 3, x = 6